2020
DOI: 10.2478/eko-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

The Alien Fraction of the Woody Flora of Yelanetskyi Step Nature Reserve, Southern Ukraine

Abstract: Results of investigations on the patterns of distribution and dispersal of alien species of trees and shrubs in the territory of a steppe protected area, Yelanetskyi Step Nature Reserve (Mykolaiv Region, southern Ukraine), are presented. We registered within this protected area 10 alien woody species. For the most widespread ones (Ulmus pumila L., Gleditsia triacanthos L., Elaeagnus angustifolia L., Robinia pseudoacacia L.), we carried out ecological analyses. In order to establish the scope of impact of ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Due to the active introduction into various types of ecosystems in many countries of the world, it is recognized as an invasive species having a high rate of adventivity (Rumlerová et al, 2016;Vítková et al, 2017;Wagner et al, 2017;Nicolescu et al, 2020;Vitková et al, 2020). The effect of R. pseudoacacia plantations on the decrease in the species diversity of forest and steppe vegetation has already been confirmed for a number of countries in Central Europe (Konaikova, Vakarenko, 2020;Montecchiari et al, 2020;Lukovičová et al, 2021). On the territory of Europe, a shift of its potential climatic niches towards the east was predicted under the conditions of climate change, with their reduction in Southern Europe and expansion in Central and North-Eastern Europe (Puchałka et al, 2021), where an increase in its invasive activity is possi-ble in the future.…”
Section: Introductionmentioning
confidence: 83%
“…Due to the active introduction into various types of ecosystems in many countries of the world, it is recognized as an invasive species having a high rate of adventivity (Rumlerová et al, 2016;Vítková et al, 2017;Wagner et al, 2017;Nicolescu et al, 2020;Vitková et al, 2020). The effect of R. pseudoacacia plantations on the decrease in the species diversity of forest and steppe vegetation has already been confirmed for a number of countries in Central Europe (Konaikova, Vakarenko, 2020;Montecchiari et al, 2020;Lukovičová et al, 2021). On the territory of Europe, a shift of its potential climatic niches towards the east was predicted under the conditions of climate change, with their reduction in Southern Europe and expansion in Central and North-Eastern Europe (Puchałka et al, 2021), where an increase in its invasive activity is possi-ble in the future.…”
Section: Introductionmentioning
confidence: 83%
“…Nowadays, the ecology and evolutionary potential of alien species are of interest to several environmental managers, and the effects of biological invasions on native communities and ecosystems are a major priority in ecology (Wardle et al, 2011;Simberloff et al, 2012;Baranová et al, 2017). Due to their faster growth, several studies use alien species to restore areas that have been heavily degraded (Ewel, Putz, 2004;Konaikova, Vakarenko, 2020). Many studies show that several herbivores were found to use alien plants, but their impact was small on alien than on native plants.…”
Section: Introductionmentioning
confidence: 99%